A Mixed Integer Linear Programming Model of Order Allocation Involving Mass Customization Logistic Service (MCLS) - Rosyidi, Cucuk Nur; Sulistiani, Nina Salsabila; Laksono, Pringgo Widyo (Mathematics Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
In an increasing business competition, a company has to improve its competitiveness by focus more on supply chain management. One of the crucial problems in supply chain deals with the allocation of orders. More and more companies are starting to adoptMass Customization Logistics Service (MCLS) mode to determine the optimal allocations of order both from suppliers and to customized logistics services at the possible lowest cost. For this purpose, a third party is needed, namely Logistic Service Integrator (LSI) in providing logistics services. However, since LSI cannot meet all customer needs, LSI chooses to outsource logistics tasks to a Functional Logistics Service Provider (FLSP). This research was developed to help decision-makers ofmanufacturing companies in making optimal decision concerning order allocations that minimize the total supply chain costs involving Mass Customization Logistics Service (MCLS).